Studies on the ecology of the paddy and fish co–culture system at Dembi Gobu microwater shed at Bako, Ethiopia - Desta, L.; Devi, L.P.; Sreenivasa, V.; Amede, Tilahun (2014)
This study on paddy cum tilapia integrated culture was carried out at Bako, West shoa zone in Ethiopia for a period of four months. The physico-chemical parameters in the water and soil, plankton and benthic fauna and yield were analysed to understand the suitability of the culture system in the study area. The water temperature in the experimental plots was recorded as a minimum of 27 ºC and a maximum 28 °C. The pH of the water declined at the end of the culture, while the dissolved oxygen increased in both paddy-fish and control plots. The CO2 and conductivity did not show considerable variation. The total alkalinity and hardness of the water increased slightly at the end of the experiment. However the concentration of ammonia remained at a very low level. The dissolved nutrients like nitrate and phosphate in the water decreased from the initial level in the paddy-fish plots. The soil nitrogen was also reduced with respect to the increase in phosphorus levels. The plankton and benthic population in the control plots were higher than in the paddy-fish plots. The texture of the soil showed increase in silt fraction, organic carbon and organic matter in all the plots. However, the yield of paddy in the paddy-fish plot was higher than in the control plots. The possible reasons for the high yield in paddy-fish plots are discussed.